2016
DOI: 10.1097/pec.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Femur Fracture Diagnosis and Management Aided by Point-of-Care Ultrasonography

Abstract: We describe a point-of-care ultrasonography to facilitate diagnosis of a femur fracture in a 13-year-old adolescent boy. Rapid detection of the fracture, which was not possible by physical examination alone, permitted immediate stabilization of the leg with traction, rapid communication with orthopedic surgeons, and facilitated analgesic therapy before transport and movement to obtain radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In line with several previous studies [ 12 , 13 , 15 , 16 ], we also demonstrated the feasibility of surveillance US for the diagnosis and closed reduction of fractures in children. We have previously shown that US can improve the reduction of radial neck fractures in children [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with several previous studies [ 12 , 13 , 15 , 16 ], we also demonstrated the feasibility of surveillance US for the diagnosis and closed reduction of fractures in children. We have previously shown that US can improve the reduction of radial neck fractures in children [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…It has the advantages of no radiation, dynamic monitoring, and easy learning and usage, as well as low cost and easy availability of equipment [ 11 14 ]. Recently, an increasing number of surgeons have also found US to be useful in the diagnosis of fractures, especially in young children, wherein the bone is not ossified and covered by cartilage, such as the forearm [ 13 ], radial head [ 12 ], femur [ 15 ], and metatarsal [ 16 ] fractures. It has also been found to be useful in the diagnosis of occult or missed fractures in children [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…MRI is available to display cartilage well, but it is impossible to determine fracture reduction quality in real-time during surgery. US nonionizing radiation has been reported in fracture diagnosis applications for children [21][22][23][24]. Very few scholars have reported the use of US-guided prying reduction for radial neck fractures [12].…”
Section: Discussionmentioning
confidence: 99%
“…One of the fundamental ALARA (‘as low as reasonably achievable’) principles is to minimize or avoid radiation whenever possible [ 17 ]. Use of US rather than radiography is a representative recommendation based on the ALARA principle, and its advantages for the diagnosis of pediatric fractures has been demonstrated [ 11 13 , 18 , 19 ]. Several reports demonstrated the efficacy and safety of US-guided reduction of fractures at the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopy has limitations in identifying pediatric bone with incomplete ossification, especially the radial head of young children [ 10 ]. Fractures could be sonographically identified along with subperiosteal hematomas, deformities, cortical disruption, and reverberating echoes [ 18 ]. Several researches demonstrated high sensitivity (86.6%–97%) and specificity (86.6%–100%) for fractures of the forearm bone and humerus [ 12 , 13 , 19 ].…”
Section: Discussionmentioning
confidence: 99%